ANALISIS KINETIKA PELEPASAN TEOFILIN DARI GRANUL MATRIKS KITOSAN - Suprianto Suprianto (Jurnal Ilmiah Manuntung, 2016)
Moment the drug dosage form development, it is important to study the drug release or dissolution that is recognized as an element in drug development. Mathematical models could help optimize the design of drugs to produce models of drug release information. Analysis of quantitative values obtained when depicting dissolution drug release profiles more easily when the mathematical concepts used to describe the drug release kinetics model. Model release of drugs known include zero order, first order, Higuchi models, models Hixon Crowell and Peppas Korsmeyer models. The purpose of this review apply mathematical concepts to study the phenomenon of drug release theophylline granules matrix made from chitosan